Dosis Efektif Inoculant Cair untuk Mempercepat Waktu Pengomposan Sampah Organik - Sri Puji Ganefati; Iswanto Iswanto; Suparjan Suparjan (Poltekkes Kemenkes Yogyakarta, 2009)
Organic waste is the biggest component (75%-80%) amongst domestic waste. The waste is potential to give negative impact on public health and environ-mental health. Further utilization of organic waste is the best way to produce organic fertilizer. However, the long duration needed for the composting process (up to 2-3 motnhs) found as major obstacle that makes people hesitate to apply this method, and therefore causing unsatisfied waste handling. One of the problem solution alternatives is to add activator (i.e. inoculant) which can accelerate the composting process. Survey held in Sukunan Village, Sleman Regency, on 4 May 2007 revealed that the addition of liquid inoculant into organic waste was able to shorten the composting time only for 2 weeks, or reduced 2-10 weeks from the normal time. However, the effective dose is has not known yet, so that it was important to conduct follow-up research to understand the most accelerating dose. The results showed that the average of composting time for each dose of the liquid inoculant were: 75 cc/lt, 11,22 days; 60 cc/lt, 13,11 days; 45 cc/lt,14,56 days; 30 cc/lt, 16,22 days; and 15 cc/t, 18,11 days. The time needed for 75cc/lt was found as the quickest and was supported by the statistical analysis using anova and t test (p-value < 0.001).